Name Disambiguation Analysis Using the Word Sense Disambiguation Method in Hadith - Ageng Prasetio; Mochammad Arif Bijaksana; Arie Ardiyanti Suryani (Universitas Hamzanwadi, 2020)
Name disambiguation is the problem solving process to find similar names in sentences. The ambiguity of names can be found in hadith of Sahih Bukhari, names